Strings of Traitors: Social Networks and the Organizational Trajectory of the Khmer Rouge - Fox, Andrew (My University, 2019)
How do social networks shape the development and trajectory of militant organizations and revolutionary parties engaged in the process of establishing political order through violence? In this dissertation, I argue that the topology of social networks becomes key to understanding how the complex web of interpersonal relationships shapes identities, interests, and collective action in the context of conflict, revolution, and state formation. Using a dataset of Khmer Rouge personnel from Democratic Kampuchea’s Southwest Zone, I examine the mechanisms of network formation and contagion to demonstrate that network structure matters a great deal to the success or failure of militant organizations as they transition into governing roles. I find that networks are the product of attraction based on shared attributes, also referred to as homophily, and self-organization that relate to network topology itself. As a consequence, these mechanisms influence the formation of networks on which informal institutions are built, violence spreads, and organizational resilience emerges.
Keywords: Political Networks; Informal Institutions; Purges; Resilience